Short chain fatty acid absorption by the human large intestine. Issue 9 (September 1978) - McNeil, N I; Cummings, J H; James, W P
Abstract : Short chain fatty acid absorption from the human rectum has been studied in 46 subjects attending an obesity clinic, using a dialysis bag technique. From a mixed electrolyte solution, acetate concentrations fell from 97.0 to 64.2 mmol/l, and sodium from 97.8 to 85.1 mmol/l with respective net absorption rates of 8.1 and 5.2 mumol/cm2/h. From a solution with mixed short chain fatty acids acetate concentration fell from 62.3 to 37.6 mmol/l, propionate from 20.2 to 11.5 mmol/l, and butyrate from 25.7 to 17.3 mmol/l with absorption rates of 5.2, 1.8, and 1.9 mumol/cm2/h. Lowering pH from 7.2 to 5.5, to test the possibility that absorption occurred by passive non-ionic diffusion, had no effect on absorption rates, although pH rose rapidly in the dialysis fluid. These results are comparable with rates of acetate absorption from the animal large intestine. The hypothesis that short chain fatty acids are not absorbed from the large gut and therefore contribute to faecal bulk by retaining water in the bowel lumen may need revision.